2018
DOI: 10.1016/j.sleh.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Sleep in a large, multi-university sample of college students: sleep problem prevalence, sex differences, and mental health correlates

Abstract: This study documents a high prevalence of poor sleep among college students, some sex differences, and distinct patterns of mental health symptoms in relation to sleep problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
304
13
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 398 publications
(365 citation statements)
references
References 50 publications
35
304
13
13
Order By: Relevance
“…This area of research is particularly important, given the growing prevalence of e‐cigarette use and potential co‐occurrence with sleep difficulties within this population. Across all groups, the mean global sleep score was well above 5, suggesting generally poor sleep, consistent with prior research documenting clinically significant sleep problems in college student populations (Becker et al., ). Global sleep health differed between never users, non‐daily users and daily e‐cigarette users, such that non‐daily and daily users of e‐cigarettes reported significantly worse sleep health than never users.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This area of research is particularly important, given the growing prevalence of e‐cigarette use and potential co‐occurrence with sleep difficulties within this population. Across all groups, the mean global sleep score was well above 5, suggesting generally poor sleep, consistent with prior research documenting clinically significant sleep problems in college student populations (Becker et al., ). Global sleep health differed between never users, non‐daily users and daily e‐cigarette users, such that non‐daily and daily users of e‐cigarettes reported significantly worse sleep health than never users.…”
Section: Discussionsupporting
confidence: 85%
“…This measure also assessed past‐month experience of sleeping problems, such as difficulties sleeping due to pain, difficulty breathing and night‐time awakenings. The PSQI has demonstrated reliability across a 4‐week time period and has been frequently used within college student samples (Becker et al., ; Lund et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Despite the importance of adolescent sleep, sleep disturbance was present in more than half of the study participants. Furthermore, the increase in sleep disturbance among the young was similar to recent studies using the PSQI [47,48], suggesting that this is not limited to this study area. In this study, sleep disturbance was more frequent in boys who participated in school sports (or clubs), skipped meals overall, and had depressive moods (mental health).…”
Section: Discussionsupporting
confidence: 88%
“…Girls are more sensitive and must pay more attention to the psychological activities of girls. Visits to students from rural areas allow students to adapt to college new life as soon as possible, and reduce the negative emotions brought about by various pressures [15][16][17][18][19][20][21][22].…”
Section: Resultsmentioning
confidence: 99%
“…Students report lack of sleep, difficulty sleeping or difficulty sleeping [2]. Studies have shown that sleep problems are common among college students [3][4][5] among them; about 20% of college students have sleep problems [6]. Despite this, many studies only examined total sleep rather than specific sleep components, highlighting the significance of further analysis of college students' sleep problems [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%